A Single Bout of Aerobic Exercise Provides an Immediate “Boost” to Cognitive Flexibility - Heath, Matthew; Shukla, Diksha (Frontiers in Psychology, 2020)
Executive function includes the core components of working memory, inhibitory control and cognitive flexibility. A wealth of studies have shown that working memory and inhibitory control are improved following a single bout of exercise; however, a paucity – and equivocal – body of work has demonstrated a similar benefit for cognitive flexibility. Cognitive flexibility underlies switching between different attentional- and motor-related goals, and a potential limitation of previous work examining this component in an exercise context is that they included tasks involving non-executive processes (i.e., numerosity, parity and language judgments). To address this issue, Experiment 1 employed a 20-min bout of aerobic exercise and examined pre- and immediate post-exercise cognitive flexibility via stimulus-driven (SD) and minimally delayed (MD) saccades ordered in an AABB task-switching paradigm. SD saccades are a standard task requiring a response at target onset, whereas MD saccades are a non-standard and top-down task requiring a response only after the target is extinguished. Work has shown that RTs for a SD saccade preceded by a MD saccade are longer than when a SD saccade is preceded by its same task-type, whereas the converse switch does not influence performance (i.e., the unidirectional switch-cost). Experiment 1 yielded a 28 ms and 8 ms unidirectional switch-cost pre- and post-exercise, respectively (ps<.001); however, the magnitude of the switch-cost was reduced post-exercise (p=.005). Experiment 2 involved a non-exercise control condition and yielded a reliable and equivalent magnitude unidirectional switch-cost at a pre- (28 ms) and post-break (26 ms) assessment (ps<.001). Accordingly, a single-bout of exercise improved task-switching efficiency and thereby provides convergent evidence that exercise can provide a global benefit to the core components of executive function.